Severe pertussis infection in infants less than 6 months of age: Clinical manifestations and molecular characterization - Paola Stefanelli; Gabriele Buttinelli; Paola Vacca; Alberto E. Tozzi; Fabio Midulla; Rita Carsetti; Giorgio Fedele; Alberto Villani; Carlo Concato; the Pertussis Study Group (Taylor & Francis Group, 2017)
We conducted a study to determine the main traits of pertussis among unimmunized infants less than 6 months of age. From August 2012 to March 2015, 141 nasopharyngeal aspirates (NPAs) were collected from infants with respiratory symptoms attending 2 major hospitals in Rome. Clinical data were recorded and analyzed. Lab-confirmation was performed by culture and realtime PCR. B. pertussis virulence-associated genes (ptxP, ptxA and prn), together with multilocus variable-number tandem repeat analysis (MLVA), were also investigated by the sequence-based analysis on the DNAs extracted from positive samples. Antibiotic susceptibility with Etest was defined on 18 viable B. pertussis isolates. Samples from 73 infants resulted positives for B. pertussis. The median age of the patients was 45 d (range 7-165); 21 infants were treated with macrolides before hospital admission. Cough was reported for a median of 10 d before admission and 18 d after hospital discharge among infected infants, 84% of whom showed paroxysmal cough. No resistance to macrolides was detected. Molecular analysis identified MT27 as the predominant MLVA profile, combined with ptxP3-ptxA1-prn2 associated virulence genes. Although our data may not be generalized to the whole country, they provide evidence of disease severity among infants not vaccinated against pertussis. Moreover, genetically related B. pertussis strains, comprising allelic variants of virulence associated genes, were identified.